Ramp-rate control smoothing methods to control output power fluctuations from solar photovoltaic (PV) sourcesA review - Sukumar S.; Marsadek M.; Agileswari K.R.; Mokhlis H. (Elsevier Ltd, 2023)
Energy storage; Low pass filters; Solar concentrators; Exponential smoothing; Moving averages; Output power fluctuations; Ramp rates; Solar photo-voltaic generators; Solar photovoltaic plants; Solar photovoltaics; Solar PVs; Solar power generation